FAKTOR-FAKTOR YANG MEMPENGARUHI CAPITAL ADEQUACY RATIO BANK KONVENSIONAL DI INDONESIA - Anggela, Anggela; Susanti, Merry (Jurnal Paradigma Akuntansi, 2023)
This research aims to obtain empirical evidence regarding the effect of banking risk (RAR), bank deposits (DAR), profitability (ROA), asset quality (AQR), liquidity, and bank size (SIZE) on the capital adequacy ratio (CAR), using 20 conventional banking companies listed on the Indonesia Stock Exchange from 2017 to 2020 with purposive sampling method. The data in this research were processed using software Eviews v12.0. The results of research that have been conducted regarding the partial significance test show that RAR, DAR, and ROA have a significant effect on the CAR, while AQR, LAR, and SIZE have no significant effect on the CAR. Simultaneously in this research RAR, DAR, ROA, AQR, LAR, and SIZE have a significant effect on the CAR.